Study of thorium and uranium isotopes activity concentration after percolation or agitation leaching, in mining lixiviation liquor samples - Aluisio Souza Reis; Roberto Pellacani Guedes Monteiro (Brazilian Journal of Radiation Sciences)
This work refers to determination of thorium and uranium isotopes in the mining lixiviation liquor samples. The analytical procedure involves sample preparation steps for rare earth elements, thorium and uranium separation, besides alpha spectrometry analysis of the isolated radionuclides. An isotopic tracer is used to determine the overall chemical yield and to ensure traceability to a standard sample from NIST. The paper presents and discusses that the chemical yield of thorium and uranium depends on the leaching method used, that is, column leaching or agitated leaching. We improved the method looking for reproducibility and isotopes isolation as required by alpha spectrometry and the method showing effective in analysis of mining liquor